Answer:
y =
+
![(1)/(18)(t^2+(2t)/(6) + (2)/(36)+(2t)/(3)+(2)/(18)+(2)/(9))](https://img.qammunity.org/2020/formulas/mathematics/college/dye3lp45ihvc7y50w9jhcptc5zr1505wgy.png)
Explanation:
y''- 9 y' + 18 y = t²
solution of ordinary differential equation
using characteristics equation
m² - 9 m + 18 = 0
m² - 3 m - 6 m+ 18 = 0
(m-3)(m-6) = 0
m = 3,6
C.F. =
![C_1e^(3t)+C_2e^(6t)](https://img.qammunity.org/2020/formulas/mathematics/college/c72pboike6i7y8uww5rzztvsbtvi9dtawm.png)
now calculating P.I.
![P.I. = (t^2)/(D^2 - 9D +18)](https://img.qammunity.org/2020/formulas/mathematics/college/bzrsq1ln92ry8jxiv5ay7n9sje9hlahhjv.png)
![P.I. = (t^2)/((D-3)(D-6))\\P.I. =(1)/(18)(1-(D)/(3))^(-1)(1-(D)/(6))^(-1)(t^2)\\P.I. =(1)/(18)(1-(D)/(3))^(-1)(1+(D)/(6)+(D^2)/(36)+....)(t^2)\\P.I. =(1)/(18)(1-(D)/(3))^(-1)(t^2+(2t)/(6) + (2)/(36))\\P.I. =(1)/(18)(1+(D)/(3)+(D^2)/(9)+....)(t^2+(2t)/(6) + (2)/(36))\\P.I. =(1)/(18)(t^2+(2t)/(6) + (2)/(36)+(2t)/(3)+(2)/(18)+(2)/(9))](https://img.qammunity.org/2020/formulas/mathematics/college/znolv400tmnshio13tlmyikxt1dr9j6pg6.png)
hence the complete solution
y = C.F. + P.I.
y =
+
![(1)/(18)(t^2+(2t)/(6) + (2)/(36)+(2t)/(3)+(2)/(18)+(2)/(9))](https://img.qammunity.org/2020/formulas/mathematics/college/dye3lp45ihvc7y50w9jhcptc5zr1505wgy.png)